2018
DOI: 10.1177/1557988318786872
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Patterns of Gay and Bisexual Men in the Momentum Health Study

Abstract: Research with male sexual minorities frequently combines gay and bisexual men as Men Who Have Sex with Men or Gay and Bisexual Men. When analyzed separately, bisexual men consistently feature negative health differentials, exemplified by higher substance use levels. This interpretation is not clear-cut because studies may combine bisexual men and women, use different dimensions of sexual orientation to define bisexuality, and/or not consider number of sexual partners as a possible confounding factor. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
(55 reference statements)
2
7
0
Order By: Relevance
“…Comparing across GBM populations, the prevalence of IDU in New Zealand is lower than in Australia, where 4.8% of GBM recruited in community samples reported recent IDU and 10.3% in an online cohort reported any lifetime IDU . In a respondent‐driven sampling study in Vancouver, 8.4% of gay‐identified men reported IDU in the previous 6 months . IDU in the past 12 months was reported by 1.9% of HIV negative and 5.2% of HIV positive GBM in the US National HIV Behavioral Surveillance survey .…”
Section: Discussionmentioning
confidence: 91%
“…Comparing across GBM populations, the prevalence of IDU in New Zealand is lower than in Australia, where 4.8% of GBM recruited in community samples reported recent IDU and 10.3% in an online cohort reported any lifetime IDU . In a respondent‐driven sampling study in Vancouver, 8.4% of gay‐identified men reported IDU in the previous 6 months . IDU in the past 12 months was reported by 1.9% of HIV negative and 5.2% of HIV positive GBM in the US National HIV Behavioral Surveillance survey .…”
Section: Discussionmentioning
confidence: 91%
“…Six studies focused on substance and drug misuse in gay, bisexual men, either alone or compared with heterosexual counterparts (Fallin-Bennett et al, 2017; Heffner et al, 2020; Ip et al, 2017; Jordan et al, 2014; Roth et al, 2018; Starks et al, 2019). Two of the studies were randomized trials; one was controlled and the second was a pilot, interventional trial.…”
Section: Resultsmentioning
confidence: 99%
“…No differences in sexual behaviors were observed among the groups (Starks et al, 2019). Roth et al (2018) conducted bivariate and multivariate analysis by comparing bisexual and gay men for substance use patterns in the Momentum Study; participants were classified based on sexual attraction, self-identity, and sexual behavior while controlling for sociodemographic, sexual behaviors, and psychosocial factors. Bivariate analysis revealed that bisexual men had higher multiple substance use in all samples (p \ .05).…”
Section: Substance and Drug Misusementioning
confidence: 99%
“…In previous studies, males with a homosexual and a bisexual orientation reported differences in the use of cybersex (more frequent Web-based sexual interactions than those reported by heterosexual males) [52]. Furthermore, people in sexual minority groups, partly due to stigma, are at increased risk of health inequalities, such as addictive disorders [53] and depression [54].…”
Section: Introductionmentioning
confidence: 99%